Pertanggungjawaban Pidana Terhadap Pelaku Yang Mencampurkan Etil Alkohol Kedalam Pangan - Balqis, Berliana; Hwian Christianto; Anton Hendrik Samudra (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
Food is important for human life to meet daily needs. Food consumed by humans must be safe, healthy and nutritionally nutritious food for the human body. Food is food or drinks consumed by humans to carry out activities. Food produced and traded must be safe food so as not to harm others. Although there are already laws and regulations governing food that is allowed to be circulated, there are still perpetrators who violate these regulations, namely trading liquor containing ethyl alcohol, which if you want to trade this type of drink, you must comply with applicable laws and regulations. Ethyl alcohol or ethanol is a liquid, clear, and colorless item which is an organic compound with the chemical formula C2H5OH. Consuming excessive amount of ethyl alcohol can be harmful to health. A ny person who uses ethyl alcohol that is not in accordance with the laws and regulations will be punished and held criminally liable.